2010
DOI: 10.1590/s0066-782x2010005000101
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazona e lesão vascular em coelhos hipercolesterolêmicos: avaliação da formação neointimal

Abstract: Background: Rosiglitazone has been the focus of extensive discussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Previous reports have pointed out that PPAR-γ receptor agonists could prevent restenosis and atherosclerosis [14,24]. Similarly, in a recent study, PPAR-γ receptor ligand rosiglitazone was shown to decrease neointima and increase luminal area of the vessels after balloon catheter injury in collesterol-fed rabbits [25]. Besides, it was reported that rosiglitazone reduced inflammatory response and retarded neointima progression after vascular injury in experimental atherosclerosis models in mouse and rats [26].…”
Section: Discussionmentioning
confidence: 96%
“…Previous reports have pointed out that PPAR-γ receptor agonists could prevent restenosis and atherosclerosis [14,24]. Similarly, in a recent study, PPAR-γ receptor ligand rosiglitazone was shown to decrease neointima and increase luminal area of the vessels after balloon catheter injury in collesterol-fed rabbits [25]. Besides, it was reported that rosiglitazone reduced inflammatory response and retarded neointima progression after vascular injury in experimental atherosclerosis models in mouse and rats [26].…”
Section: Discussionmentioning
confidence: 96%
“…That study is part of our research line in an animal model (rabbits) submitted to a hypercholesterolemic diet and then treated with functional food (linseed and resveratrol) 1 . Within our research line we also work with medications and arterial lesions in hypercholesterolemic rabbits 2,3 . All such models used rabbits, whose hypercholesterolemia had been caused by either the Sigma Aldrich product or lyophilized eggs.…”
Section: Response Lettermentioning
confidence: 99%
“…Studies with dietary formulations require the description of all components included in the diet, because they vary considerably in commercial formulations (especially antioxidants) and might jeopardize the results and reproducibility of the study 2 .…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation